2020
DOI: 10.3390/cells9010254
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Sensibility—HIV-1 and the Innate Immune Response

Abstract: Innate immunity represents the human immune system’s first line of defense against a pathogenic intruder and is initiated by the recognition of conserved molecular structures known as pathogen-associated molecular patterns (PAMPs) by specialized cellular sensors, called pattern recognition receptors (PRRs). Human immunodeficiency virus type 1 (HIV-1) is a unique human RNA virus that causes acquired immunodeficiency syndrome (AIDS) in infected individuals. During the replication cycle, HIV-1 undergoes reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 119 publications
0
63
0
Order By: Relevance
“…In a previous study, it was found that when the human airway is exposed to invading pathogens, the congenital immune process is rapidly induced (Lebold, Jacoby & Drake, 2016). The congenital immune system is the first line of defense in the human immune system (Yin et al, 2020). When the body is infected by foreign agents, inflammatory reactions will occur first (Kimbrell & Beutler, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was found that when the human airway is exposed to invading pathogens, the congenital immune process is rapidly induced (Lebold, Jacoby & Drake, 2016). The congenital immune system is the first line of defense in the human immune system (Yin et al, 2020). When the body is infected by foreign agents, inflammatory reactions will occur first (Kimbrell & Beutler, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we also found that signaling related to immune response, Fcepsilon receptor signaling pathway, viral process, and symbiosis, encompassing mutualism through parasitism signaling affected by the COVID-19 targeting human cellular miRNAs (Table.6). The signaling mentioned above is important to fight against viral infections [45][46][47][48]. Both KEGG and GO pathway analysis revealed that COVID-19 targeting human cellular miRNAs are involved in the number of age-related complications.…”
Section: And Supplementarymentioning
confidence: 99%
“…In a previous study, it was found that when the human airway is exposed to invading pathogens, the congenital immune process is rapidly induced (Lebold et al 2016). The congenital immune system is the first line of defense in the human immune system (Yin et al 2020). When the body is infected by foreign agents, inflammatory reactions will occur first (Kimbrell & Beutler 2001).…”
Section: Discussionmentioning
confidence: 99%